PERTUMBUHAN VEGETATIF DAN GENERATIF Stachytarpeta jamaicensis(L.) Vahl - Solikin Solikin (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2013)
Stachytarpeta jamaicensis  belongs to  family   Verbenaceae believed to cure malaria, scabies, headaches,stimulant, tonic, expectorant and fever. The research aims to determine  vegetative and generative growth of Stachytarpeta jamaicensis was conducted in Purwodadi Botanic Garden  in October 2012  -  June 2013 by observing 9 plants  grouped in 3 replications. Seedlings with 6-12 leaves were  planted in polybags  with diameter 13 cm,  height 16 cm   filled  with soil media ‘katel’ (soil stream  sediment).  The plants placed outside the glass house with  light penetration  about 20%. Growth observations conducted every week to high, leaf  number, shoot/branch number,  spike number, spike  length, early flowering and fruit maturity of the plants.  The results showed that  the plant height,  the leaf number, the shoot  and branch and  the spik s number  of the plants was  increasing linearly  up to the age of 90 days after planting (DAP). Early and late flowering varied  each   20-40 DAP  and 69-83 DAP.  The length of spikes  growth following the sigmoid curve and the   fruits mature  at   the age of 38 days after  fertilization.  Keywords: Growth, Stachytarpeta Jamaicensis, Vegetative, Generative